Analisis Model CIPP, Iluminatif, dan Responsif dalam Evaluasi Kurikulum Pendidikan Agama Islam - Aprina Noor Latifah; Salamah Salamah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study is based on the importance of curriculum evaluation in ensuring the achievement of educational goals, particularly in Islamic Religious Education (PAI), which emphasizes not only cognitive development but also character building and the cultivation of religious values among students. Various evaluation models have been developed to support curriculum evaluation, including the CIPP, illuminative, and responsive models. However, studies that examine these three models simultaneously and analyze their relevance to the development of the PAI curriculum remain limited. Therefore, this study aims to analyze the characteristics of the CIPP, illuminative, and responsive evaluation models and to examine their relevance in the evaluation and development of the Islamic Religious Education curriculum. This research adopted a qualitative approach with a library research design. Data were obtained through document analysis of books, journal articles, and other related scholarly materials and were analyzed using content analysis involving data reduction, data display, and conclusion drawing. The findings indicate that the CIPP model provides the most comprehensive evaluation framework by examining context, input, process, and product components. The illuminative model emphasizes an in-depth understanding of curriculum implementation in real educational settings, whereas the responsive model focuses on the needs and perspectives of stakeholders. Each model has distinct characteristics, strengths, and limitations; therefore, its application should be adjusted to the objectives and context of the evaluation. These findings imply that the use of a single model or a combination of evaluation models can provide more comprehensive information to support the effective and sustainable development of the PAI curriculum.